Pedagogical management in the content of professional training of future preschool education masters - Marianna Matishak (Vasyl Stefanyk Precarpathian National University, 2017)
This article summarizes the features of the training of future masters in Pre-school Education to implement educational management, clarified its role in the professional development specialists. Thesis there is determined and analyzed the semantic content of the various aspects of educational management, namely cognitive-semantic, active, reflective and motivational value. Key words: pedagogical management, future masters, pre-school education, managerial competence.